Chitosan hydrogel micro-bio-devices with complex capillary patterns via reactive-diffusive self-assembly. (November 2019) - Adibnia, Vahid; Mirbagheri, Marziye; Latreille, Pierre-Luc; Faivre, Jimmy; Cécyre, Bruno; Robert, Jordan; Bouchard, Jean-Francois; Martinez, Vincent A.; Delair, Thierry; David, Laurent; Hwang, Dae Kun; Banquy, Xavier
Graphical abstract: Abstract: We present chitosan hydrogel microfluidic devices with self-assembled complex microcapillary patterns, conveniently formed by a diffusion-reaction process. These patterns in chitosan hydrogels are formed by a single-step procedure involving diffusion of a gelation agent into the polymer solution inside a microfluidic channel. By changing the channel geometry, it is demonstrated how to control capillary length, trajectory and branching. Diffusion of nanoparticles (NPs) in the capillary network is used as a model to effectively mimic the transport of nano-objects in vascularized tissues. Gold NPs diffusion is measured locally in the hydrogel chips, and during their two-step transport through the capillaries to the gel matrix and eventually to embedded cell clusters in the gel. In addition, the quantitative analyses reported in this study provide novel opportunities for theoretical investigation of capillary formation and propagation during diffusive gelation of biopolymers. Statement of Significance: Hydrogel micropatterning is a challenging task, which is of interest in several biomedical applications. Creating the patterns through self assembly is highly beneficial, because of the accessible and practical preparation procedure. In this study, we introduced complex self-assembled capillary patterns in chitosan hydrogels using a microfluidic approach. To demonstrate the potential application of these capillary patterns, a vascularized hydrogel with microwells occupied by cells was produced, and the diffusion of gold nanoparticles travelling in the capillaries and diffusing in the gel were evaluated. This model mimics a simplified biological tissue, where nanomedicine has to travel through the vasculature, extravasate into and diffuse through the extracellular matrix and eventually reach targeted cells.